FORMULATION AND IN VITRO EVALUATION OF EZETIMIBE RAPIDMELTS - RANI, T NEELIMA; MUZIB, Y INDIRA (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The main objective of the present research was formulation and evaluation of ezetimibe rapidmelts. Methods: As ezetimibe comes under Class II drug, solubility of the drug should be increased before formulation. For that solid dispersions were prepared with β-CD and PVP K-30 using coevaporation and kneading method. Among those solid dispersions prepared with β-CD (1:1.5) using coevaporation method has given better drug entrapment values compared to other solid dispersions. Those solid dispersions were formulated as rapidmelts using direct compression. In direct compression method, rapidmelts were prepared using superdisintegrants such as crospovidone, croscarmellose sodium, and starch 1500. Those are evaluated for both pre-compression and post-compression parameters. Rapidmelts of ezetimibe were prepared using sublimation method with subliming agents camphor, urea, and ammonium bicarbonate. The concentrations of subliming agents were found to be 2.5, 5.0, and 7.5%. Results: Rapidmelts prepared using direct compression and sublimation methods were evaluated for weight variation, hardness, friability, % drug content, and disintegration time. The best formulation was subjected to stability testing for 6 months at 25°C/60% RH and 40°C/75% RH. All the prepared formulations compiled with the pharmacopeial limits. In all the formulations, results suggest that E12 formulation has given the best results. Conclusion: From the result, it was concluded that rapidmelts prepared using sublimation method which has given better result than direct compression method. That final formulation was further evaluated for in vivo studies using rabbits.